Audit Sistem Informasi Aplikasi Presensi Online Karyawan GreatDay HR Menggunakan Framework Cobit 5 - Mia Nivia Sari; Besus Maulana Shulton (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
PT. Intan Salsabila, also known as Intan International Tour & Travel, is a company that organizes Hajj and Umrah services. Currently the company implements an attendance system using the Android application into 4 data conditions, namely employee attendance, collection of employee attendance data one day before entering salary according to employee data provided, overtime presence, and business trip presence. This study will focus on the system of overtime attendance in the form of applications and android application sites. The purpose of an attendance system audit is to find out that the attendance system that has been implemented is running properly. This research was started from conducting a literature study to support the research. In collecting and observing data, this study used survey methods and interviews with relevant informants and confirmed documents. The domains chosen in this study are Delivery, Service and Support (DSS) and validating and (MEA01.01) in evaluating to measure presence solutions and services. The research results show that . PT. Intan Salsabila, it can be concluded from the results of the questionnaire order that the domain with the highest score, namely the DSS01.01 Perform Operational Procedure domain, obtained a maturity level value of 10.62 with a Fully Achieved achievement value, received an Optimized Level in IT capabilities, a gap value of 5.62 from target level 5 in the first order, DSS02.02 Record, classify, and priortise requests and incidents and DSS01.03 has a GAP line of -055, the smallest value that must be repaired must be repaired again in the application and the user. For other domains it must be maintained so that the application or user who uses it must maintain the application